2004
DOI: 10.1177/1069072704266673
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Thinking and Difficulties in Career Decision Making

Abstract: The present study examined the relationships between two measures of career readiness and difficulties—the Career Thoughts Inventory (CTI) and the Career Decision-Making Difficulties Questionnaire (CDDQ)—as well as the relations between these measures and the individual’s degree of decidedness regarding his or her career plans. A total of 192 university students enrolled in a career-planning class filled out both questionnaires. As hypothesized, the two measures overlapped significantly. There was a highly sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 41 publications
(75 reference statements)
5
56
0
6
Order By: Relevance
“…In the career development literature, career thoughts have significantly influenced the career choice process (Kleiman, Gati, Peterson, Sampson, Reardon & Lenz, 2004;Strauser, Lustig, Keim, Ketz & Malesky, 2002). In particular, negative career thoughts have yielded significant relationships with career-related anxiety (Dahl, Austin, Wagner & Lukas, 2008;, and this anxiety limits career development behaviour (Carr, 2004).…”
Section: Trends From the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In the career development literature, career thoughts have significantly influenced the career choice process (Kleiman, Gati, Peterson, Sampson, Reardon & Lenz, 2004;Strauser, Lustig, Keim, Ketz & Malesky, 2002). In particular, negative career thoughts have yielded significant relationships with career-related anxiety (Dahl, Austin, Wagner & Lukas, 2008;, and this anxiety limits career development behaviour (Carr, 2004).…”
Section: Trends From the Literaturementioning
confidence: 99%
“…In the career development literature, negative career thoughts link empirically to greater levels of perfectionism and career indecision (Osborn, 1998), depression and career indecision (Saunders, Peterson, Sampson & Reardon, 2000), career indecision (Austin, Wagner & Dahl, 2003;Kleiman, Gati, Peterson, Sampson, Reardon & Lenz, 2004;Wright, 2001) and career indecisiveness (Austin, Wagner & Dahl, 2004;.…”
Section: Trends From the Literaturementioning
confidence: 99%
“…This includes locus of control (Lease, 2004), self-efficacy (Sidiropoulou-Dimakakou, Mylonas, Argyropoulou, & Tampouri, 2012), dysfunctional thinking (Kleiman et al, 2004;Sidiropoulou-Dimakakou et al, 2012), and personality traits as measured by the Big Five model of personality (Di Fabio & Palazzeschi, 2009). It has been found that a more external locus of control predicted more career decisionmaking difficulties (Lease, 2004), lower levels of self-efficacy were associated with both more dysfunctional thoughts and more career decision-making difficulties (Sidiropoulou-Dimakakou et al, 2012), and, finally, lower levels of extroversion and higher levels of neuroticism were associated with more career decision-making difficulties (Di Fabio & Palazzeschi, 2009).…”
mentioning
confidence: 99%
“…Dla osób w sytuacji decyzji zawodowej opracowano model podejmowania decyzji dotyczących wyboru kariery (Gati, Saka, 2001a). Jego podstawowym celem jest ułatwienie procesu decyzyjnego (Kleiman i in., 2004). Autorzy wskazują, że dla danej osoby optymalny jest wybór, który maksymalizuje oczekiwaną (subiektywną) swoją użyteczność (Gati i in., 2010).…”
Section: Trudności W Podejmowaniu Decyzji Zawodowychunclassified
“…Szczególnie dysfunkcjonalne przekonania pogarszają jakość podejmowanej decyzji, co przekładać się może na trudności w rozpoczynaniu i realizacji kariery (Kleiman i in., 2004). W kontekście niniejszych badań można wskazać wysokie nasilenie lęku jako cechy i jego związek z wyższym nasileniem trudności.…”
Section: Dyskusja Wynikówunclassified